Critical Thinking Skills: Improvement Through Learning Ownership-PBL Approach on Students - Listyorini, Dwi; Prabaningtyas, Sitoresmi; Mustakim, Siti Salina; Risqillah, Ulfa (Sekolah Pascasarjana Universitas Negeri Malang (UM), 2025)
Through a method called